Fungus-mediated preferential bioleaching of waste material such as fly - ash as a means of producing extracellular, protein capped, fluorescent and water soluble silica nanoparticles - Khan, Shadab Ali; Uddin, Imran; Moeez, Sana; Ahmad, Absar (PLoS One, 2014)
In this paper, we for the first time show the ability of the mesophilic fungus Fusarium oxysporum in the bioleaching of waste material such as Fly-ash for the extracellular production of highly crystalline and highly stable, protein capped, fluorescent and water soluble silica nanoparticles at ambient conditions. When the fungus Fusarium oxysporum is exposed to Fly-ash, it is capable of selectively leaching out silica nanoparticles of quasi-spherical morphology within 24 h of reaction. These silica nanoparticles have been completely characterized by UV-vis spectroscopy, Photoluminescence (PL), Transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Energy dispersive analysis of Xrays (EDAX).